1978
DOI: 10.1111/j.1365-3083.1978.tb00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Changes in T and B Lymphocyte Responses to Herpes Simplex Virus in Man

Abstract: Lymphocytes of seven patients with primary herpetic infection, twenty-three patients with recurrent herpes labialis and of nineteen control subjects were separated into T and B enriched cells by the use of nylon wool columns. In the absence of a herpetic infection the thymidine incorporation and macrophage migration inhibition responses to herpes simplex virus (HSV), Candida albicans and PPD, and the thymidine incorporation induced by PHA were functions of T cells. When a herpetic infection was present, the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Instead, the disease episode increased the T lymphocyte response to HSV-1 antigen, as shown in other studies (7)(8)(9)(10). The enhanced T cell response during recurrent disease may reflect the activity of cells in immunologically normal individuals which are more important in restricting the disease to a local site as suggested by Russell (40) rather than governing the frequency of recurrences.…”
Section: Effect Of Recurrent Infection On Lymphocytementioning
confidence: 58%
See 1 more Smart Citation
“…Instead, the disease episode increased the T lymphocyte response to HSV-1 antigen, as shown in other studies (7)(8)(9)(10). The enhanced T cell response during recurrent disease may reflect the activity of cells in immunologically normal individuals which are more important in restricting the disease to a local site as suggested by Russell (40) rather than governing the frequency of recurrences.…”
Section: Effect Of Recurrent Infection On Lymphocytementioning
confidence: 58%
“…The significance of lymphocyte transformation as a correlate of susceptibility to recurrent HSV infection is not established. Defects in transformation to HSV antigen associated with acute disease have been detected by some investigators (6), but not by others (7)(8)(9)(10)(11). Defects in lymphokine production in vitro, for example, in migration inhibiting factor and interferon production have been reported during acute HSV infection (7,12).…”
mentioning
confidence: 98%
“…Blast transformation and macrophage migration inhibition response to HSV antigens have been studied during recurrent episodes of the disease. There appears to be an increase in blast transformation and a concomitant decrease in macrophage migration inhibition (Shillitoe et al 1978). Interferon production also seems to be increased, while the cell type responsible for blast transformation appears to be the T-cell and for interferon production, the B-cell (Rasmussen & Merigan 1978).…”
Section: Viral Diseasementioning
confidence: 94%
“…Recurrent infections develop in the presence of high titers of virus-specific neutralizing antibody, and severe herpetic infections occur in individuals with impaired cell-mediated immunity (15). For these reasons, investigators have examined various aspects of cellular immunity in patients with HSV infections (17,20,21,24,25); however, most previous studies have focused on recurrent disease, and there is little information available regarding cell-mediated immunity in initial HSV infections. Recently, we demonstrated that the proliferative response of lymphocytes from patients with initial genital HSV infection reached a maximum during the 4th week of the disease and that the magnitude of the response was inversely correlated with the duration of viral shedding and the persistence of symptoms (4).…”
mentioning
confidence: 99%